THE EFFECT OF PATTERN CONFORMITY ON THE USE OF SHOELAST WITH DIFFERENT HEIGHTS - Abimanyu Yogadita; Sanjaya Nugraha; Mianto Rochmadi (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2024)
Pattern is an important component in the shoe making process. The suitability of the pattern in making shoes will affect the comfort of wearing when the shoes are used. This is because the pattern is made from a shoe last, so the pattern takes the size details from the shoe last used. However, in practice, patterns are sometimes used to make shoes of different sizes. Based on this problem, it is necessary to conduct research regarding the application of pattern conformity to the use of shoe last that have different heights. The method used in this research is an experimental method. The results of this research are that patterns that do not match will be difficult to use in shoe last that have differences in heel height. So that the use of a pattern that matches the shoe last when making shoes must match the shoe last used in making the pattern.